Clinical management of the transplant patient - Kuo, Paul C; Schroeder, Rebecca A; Johnson, Lynt B (Arnold, 2001)
This book provides a comprehensive overview of solid organ transplantation for residents, fellows and other personnel working in Transplant Units. It addresses the clinical management of the transplant patient from pre-transplant evaluation through surgery to outpatient follow-up. Emphasis is given to the information required for day to day management. This information is presented in a concise and practical format for easy access.
Keywords: transplantologie; transplantace orgánů; Perioperative Care; perioperační péče; Organ Transplantation